Pravna narava in vsebina korporacijskega vrnitvenega zahtevka delniške družbe - Prostor, Jerneja (Podjetje in delo, 2020)
In accordance with the position expressed by the German Federal Supreme Court of Justice in 2013 (BGH II ZR 179/12), the contract, which is a basis for a disguised distribution, is not void. The contracting parties can adjust the contract unanimously to the market conditions. If they do not reach consensus and have already performed in accordance with the contract, then both of the contracting parties can claim the performed back in analogous application of par. 346 BGB, the purpose of which is the establishment of the previous state (restitution). This conclusion deviates from the prevalent theory and case law in Austria and Slovenia, according to which the contract in such cases is void and both of the contracting parties can claim back already performed. However, the purpose of the company`s claim is in accordance with the company law in restitution, whereas the shareholder claim has an enrichment nature. The position in Slovenia should follow the German view, since Slovenian company law as well provides a special sanction for violation of rules on prohibited payments, i.e. return of prohibited distributions. Nevertheless, the legal consequences would still not be the same, since the regulation on the law of obligations in Austria and Slovenia differs from the one in Germany.
Keywords: company`s claim for reimbursement; delniške družbe; enrichment; joint stock company; nična pogodba; obogatitev; osnovni kapital; prepoved vračila vložkov; prohibition to refund; share capital; void contract; vrnitveni zahtevek